Entre o TIbre e o Amazonas: a romanização serpenteia a igreja de Manaus (1916-1958) - SOARES, Elisângela Socorro Maciel (Universidade Federal do Pará, 2024)
The thesis entitled “Between the Tiber and the Amazon: The romanization winds through the Church of Manaus (1916-1958)” presents a historical rescue of the trajectory of the Diocese/Archdiocese of Manaus, starting from the concern of the Church/State relationship, the actions of the Episcopate and the Laity during the second and third phases of the Romanization process, a project that gained more strength during the Papacy of the Pios, emphasized here in the governments of Pio XI (1922-1939) and Pio XII (1939-1958). The romanizing actions are visualized here, in three chapters, in the administration of the leading Episcopate of the Church of Manaus, in its three diocesan phases, the first being presented in an introductory form, and in the first archdiocesan phase: Dom José Lourenço da Costa Aguiar (1894- 1905) and Dom Frederico Benício de Sousa Costa (1907-1913), the first Phase of the Episcopate; Dom João Irineu Joffily and Dom Friar Basílio Manuel Olímpio Pereira (1926-1941), the second Phase of the Episcopate; Dom João da Mata Andrade e Amaral (1941-1948) and Dom Alberto Gaudêncio Ramos (1949-1952), the third Phase of the Episcopate; the latter being elevated to Archbishop by the same bull of elevation of Manaus to Archdiocese, in 1952, constituting the first archdiocesan phase, until the beginning of 1958. The last chapter brings the other ecclesiastical face of the Diocese/Archdiocese, in line with the Episcopate and with the directives of the Holy See, the laity, who assume a differentiated role in this period cut by the thesis, and, that in the case of the Church of Manaus , visibility was given to the two most active: Pia Union of the Daughters, with expressive leadership from 1913 until the 1930s; and Catholic Action, which assumed the leadership of Catholic associations from this decade onwards, and with its sectors reaching various instances of society. Thus, the two ecclesial faces that make up the Church of Manaus are presented historically, within the outline, problematization and context brought by this thesis.